Repair of Post-Infarction Ventricular Septal Rupture and Ventricular Aneurysm: A Case Report - Das, Debasish; Rahman, C M Mosabber; Hossain, Md Sazzed Al; Mursalin, Golam; Khan, Omar Sadeque; Hoque, Md Rezwanul (Eastern Medical College Journal, 2023)
Ventricular septal rupture is one of the fatal complications of acute myocardial infarction. With the advancement of medical management and availability of emergency cardiac care, the incidence of post infarct ventricular septal rupture has reduced considerably. We report a case, unique in being a late presentation of post infarct ventricular septal rupture with left ventricular aneurysm. The Ventricular septal rupture was repaired using a PTFE patch, followed by reinforced linear closure of aneurysm by a glutaraldehyde treated pericardial felt and revascularization using reversed saphenous vein graft to left anterior descending artery. The patient survived surgery with an uneventful postoperative course. Eastern Med Coll J. July 2023; 8 (2):75-77